A Comparison of Tests for Detecting Prior Exposure to Coxiella burnetii for Use with Q-VAX in Australian Human Q Fever Vaccination - Stephen Graves; Jennifer Robson; Anja Scholzen; Richard Dzeng; Francisca Powell-Romero; Jennifer Evans; John Stenos; Meg Jeppesen; Milou L. C. E. Kouwijzer; Jordi Lankhof; Susan Raju Paul; Tatiana Proboste Ibertti; et al. (Vaccines, 2025)
Background/Objectives: Q-VAX vaccine, approved in Australia, prevents Q fever. However, individuals with prior Coxiella burnetii (Cb) infection have an increased risk of adverse reactions, requiring pre-vaccination screening by an intradermal hypersensitivity skin test for cell-mediated immune memory and a serological assay for anti-Cb antibodies. The week-long interval for skin test assessment limits efficient vaccination. This study evaluated a standardized interferon-γ release assay (IGRA) as a potential skin test alternative. Methods: Immune assays were compared in Australian populations with different incidences of prior Cb exposure. Cell-mediated immunity was assessed by the Q-VAX skin test and IGRA. Serological status was evaluated with established diagnostic assays. Hypothetical vaccine eligibility decisions using combined IGRA and serology results were compared with actual clinical decisions made using current guidelines. Results: All tests performed better in detecting prior infection than in detecting prior vaccination. Only the IGRA identified all individuals with a known history of Q fever. Agreement between the skin test and IGRA was limited. Moderate agreement was observed between hypothetical vaccine eligibility determinations based on IGRA plus serology results and actual clinical decisions. IGRA-positive but serology- and skin test-negative individuals received Q-VAX without clinically significant side effects, suggesting that elevated IGRA responses alone are not predictive of susceptibility to vaccine reactogenicity. Conclusions: The IGRA is not yet a suitable skin test replacement when assessing eligibility for Q fever vaccination, despite the significant limitations of the latter. We offer recommendations for designing future studies that might allow the development of appropriate guidelines for IGRA use in vaccine eligibility screening.